Pre-service teachers’ academic judgments of overweight students - Müller, Barbara C. N.; Oude Groote Beverborg, Arnoud; Glock, Sabine (Social psychology of education, 2017)
Overweight children in schools can become victims of stereotyping and discrimination from both peers and teachers. Research on stereotypical expectations and impression and judgment formation has suggested that teachers might rely on their negative stereotypical expectations when judging students. In the present study, we experimentally investigated whether pre-service academic subject teachers’ judgments about students were biased through stereotypical expectations about students’ weights. Pre-service teachers were presented with a case report of an overweight- and a normal-weight student, and judged their academic performance and social skills. Results demonstrated that the overweight student was judged as performing better compared to his normal-weight counterpart academically while perceived social skills did not differ. Response latencies suggest that these findings relate to pre-service teachers’ positive stereotypical beliefs about overweight students. These findings inspire to further investigate this surprising positivity bias and develop trainings for pre-service students to overcome other stereotypical expectations, which should ideally lead to evaluations based solely on actual academic performance and not stereotypical expectations, whether they are positive or negative.